The Impact of Corporate Governance on Employee Engagement with the Moderating Role of Leadership Style in Nepalese Commercial Banks (Management Dynamics, 2024)
Corporate governance plays a crucial role in enhancing employee engagement by fostering transparency, ethics, and accountability, which cultivates trust, fairness, and inclusive decision-making. Leadership style further strengthens the relationship between corporate governance and employee engagement by promoting ethical behavior, encouraging open communication, and empowering employees to contribute to organizational objectives. This study seeks to explore the impact of leadership style on the relationship between corporate governance and employee engagement in Nepalese commercial banks. Data were gathered from 352 respondents, including managerial and officer-level employees across various commercial banks, through a structured questionnaire using a convenience sampling method. The data were analyzed using Process Macro 4. The results indicate that leadership style fully moderates the relationship between corporate governance and employee engagement. This study highlights the importance of organizations investing in leadership development programs to effectively enhance both corporate governance and employee engagement. By establishing clear policies, ensuring fairness, and fostering a culture of accountability, corporate governance motivates employees to align with the organization’s values and objectives.